Stimulated bacterioplankton growth and selection for certain bacterial taxa in the vicinity of the ctenophore Mnemiopsis leidyi - Dinasquet, Julie; Granhag, Lena M.; Riemann, Lasse (Frontiers in Microbiology, 2012)
Episodic blooms of voracious gelatinous zooplankton, such as the ctenophore Mnemiopsis leidyi, affect pools of inorganic nutrients and dissolved organic carbon by intensive grazing activities and mucus release. This will potentially influence bacterioplankton activity and community composition, at least at local scales; however, available studies on this are scarce. In the present study we examined effects of M. leidyi on bacterioplankton growth and composition in incubation experiments. Moreover, we examined community composition of bacteria associated with the surface and gut of M. leidyi. High release of ammonium and high bacterial growth was observed in the treatments with M. leidyi relative to controls. Deep 454 pyrosequencing of 16S rRNA genes showed specific bacterial communities in treatments with M. leidyi as well as specific communities associated with M. leidyi tissue and gut. In particular, members of Flavobacteriaceae were associated with M. leidyi. Our study shows that M. leidyi influences bacterioplankton activity and community composition in the vicinity of the jellyfish. In particular during temporary aggregations of jellyfish, these local zones of high bacterial growth may contribute significantly to the spatial heterogeneity of bacterioplankton activity and community composition in the sea.